Determination of Verapamil in Human Plasma by Tandem Mass Spectrometry - BAVISKAR, DHEERAJ; SHARMA, RAJESH; JAIN, DINESH (Asian Journal of Chemistry, 2010)
An analytical method based on liquid chromatography with positive ion electrospray ionization (ESI) coupled to tandem mass spectrometry detection (LC-MS/MS) was developed for the determination of verapamil in human plasma using ondansetron as the internal standard. The analyte and internal standard were extracted from the plasma samples by liquid-liquid extraction. The separation of verapamil and ondansetron was achieved on a reversed phase (C18) column with a mobile phase consisting of 10 mM ammonium acetate:methanol (20:80 % v/v). The linearity range was 1 to 496 ng/mL. Inter-day and intra-day accuracy and precision was found 98.08-102.19, 7.80-10.94 and 99.74- 106.55, 4.90-7.63, respectively.